Reflecting on Existential Threats Elicits Self-Reported Negative Affect but No Physiological Arousal - Poppelaars, Eefje S.; Klackl, Johannes; Scheepers, Daan T.; Mühlberger, Christina; Jonas, Eva (Frontiers in Psychology, 2020)
There is mixed evidence whether reflecting on existential threat increases negative affect and thereby elicits subjective arousal and physiological activation. Additionally, it is debated whether different existential and non-existential threats elicit different arousal responses, although systematic comparisons are lacking. The current study explored affective, subjective, and physiological arousal responses while comparing several existential threats with a non-existential threat and with a control condition. 171 undergraduate students were randomly allocated to one of four existential threat conditions: mortality salience (MS), freedom restriction, uncontrollability, and uncertainty; or to the non-existential threat condition: social-evaluative threat (SET); or to a control condition (TV salience). Self-reported positive/negative affect was measured before and after reflection, while subjective arousal and physiological activation (electrodermal, cardiovascular, and respiratory) were measured on a high time-scale during baseline and reflection. Results showed larger increases in self-reported negative affect – as compared to the control condition – for all existential threat conditions, while there were no differences between the control condition and threat conditions regarding positive affect, subjective arousal, skin conductance, respiratory rate, and respiratory sinus arrythmia. There were subtle differences between existential and non-existential threat conditions, most notably in affective responses. Correlations showed positive associations between negative affect and subjective arousal and between trait avoidance and subjective arousal. This study is the first to systematically compare affective, subjective, and physiological changes in arousal due to reflecting on different existential threats, as well as one non-existential threat. We showed that, as compared to a control condition, reflecting on threats has a large impact on negative affect, but no significant impact on positive affect, subjective arousal, and physiological activation.